AN ASSESSMENT OF THE IMPACT OF THE CONSTRUCTION SECTOR ON THE GROSS DOMESTIC PRODUCT (GDP) OF NIGERIA - SAKA, NAJIM; T. F, Adegbembo (Journal of Surveying, Construction and Property, 2022)
The construction sector makes significant contribution to employment, domestic capital formation and the Gross Domestic Product (GDP). However, the Nigerian Construction Sector (NCS) is beset by a number of challenges including over-dependent on foreign inputs, economic volatility, low linkages and poor project cost and time performance. The study investigates the impact of the construction sector on the GDP using a 47-year annualized Time Series Data (TSD) gotten from the United Nations Statistics Department (UNSD) database. The study employs econometric methodology which involves series of tests and procedures including tests for unit root and cointegration and Polynomial Distributed Lag (PDL) model. The summary of the estimates including the PDL indicate significant effect of the construction sector on the GDP only when the lag of the GDP is not included as one of the regressors. The study concludes that the effect of the construction sector on the GDP is not robust. Finally, the study recommends for a new national housing and transport infrastructure policy for the sustainable development of the Nigerian constructed infrastructure facilities. The study has demonstrated the relationship between the NCS and GDP. The study added to the body of knowledge by using time series data involving the use of distributed lag model (DLM), autoregressive distributed lag (ADL) model and polynomial distributed lag (PDL) model to assess the relationship.